RANCANG BANGUN SISTEM INFORMASI ATM BERAS RASKIN DENGAN MENGGUNAKAN RADIO FREQUENCY IDENTIFICATION (RFID) - Muhammad Hidayat Tullah; Tiena Gustina Amran; Dedy Sugiarto (JURNAL TEKNIK INDUSTRI, 2016)
Indonesian Goverment launched rice program for poor households, called as ProgramBeras Miskin (RASKIN) with the aim to help poor families in the avaibility of rice. Raskinprogram is still raises problems so that the benefits received are not significant for poor families.The purpose of this study was to describe about distribution proccess of Raskin especially inBekasi City, mapping constraints experienced in the implementation of Raskin distribution andmake a design of Rice ATM information system for Raskin distribution in Bekasi City. Theresearch methodology used in this study began with observation of the research object to obtainpreliminary data in Raskin general guidlines, number of seeds of households needs and Raskinbeneficiary mapping in study area. Research result is a design of system information with RFIDimplementation to improve the effectiveness and the achievement of Raskin objectives program.Keywords: Raskin, RFID, System Information.